139 Clinical outcomes of patients excluded from cardiac investigation in the NICE guidelines for chest pain of recent onset. (16th May 2012) - Patterson, C; Ahmed, N; Nicol, E; Bryan, L; Bell, D
Abstract : Introduction: NICE guidance for the investigation of chest pain of recent onset1 recommends clinical assessment and risk stratification within a diagnostic algorithm. Patients with pain considered "non-anginal", and those with atypical/typical anginal pain but a likelihood of coronary artery disease (CAD) <10% are not routinely recommended for cardiac investigation. This study sought to assess whether clinical outcomes support these patients being considered at low risk of CAD. Methods: 557 consecutive patients (50.4% male; median age 55 yrs) attending rapid access chest pain clinics (RACPC) at two hospitals were risk stratified using NICE criteria. Frequency of admission with suspected angina, diagnosis of CAD and incidence of major adverse cardiac events (MACE: myocardial infarction (MI), cerebrovascular accident (CVA), emergency revascularisation or cardiac-related death) were compared for all risk categories at 6 months. Results: Of 360/557 patients with "non-anginal" pain, 14 (3.9%) were subsequently admitted with angina, 34 (9.4%) were diagnosed with CAD, 3 (0.8%) with MI and 2 (0.6%) with CVA. This group accounted for 36.9% of all patients diagnosed with CAD and 38.5% of all patients with MACE. Of 10/557 patients with atypical/typical anginal pain and a likelihood of CAD <10%, 1 (10%) was diagnosed with CAD. None were admitted with angina or diagnosed with MACE. This group accounted for 1.1% of all patients diagnosed with CAD. Conclusions: This study suggests one in ten patients routinely excluded from cardiac investigation by the NICE algorithm have CAD and just over one in a hundred of them have a MACE episode. Although these patients are considered low risk, they account for one third of adverse cardiac events in patients attending RACPC.